2000
DOI: 10.1021/ja002436k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptides as Molecular Adapters for a Pore-Forming Protein

Abstract: Recently, cyclodextrins were shown to act as adapters for the pore-forming protein staphylococcal α-hemolysin (αHL). The bagel-shaped molecules bind in the lumen of the transmembrane channel formed by αHL and alter the properties of the pore. For example, the unitary conductance is reduced, and organic molecules can act as channel blockers by binding to the cavity within the cyclodextrin adapter. In a search for a class of adapters more versatile than the cyclodextrins and amenable to preparation as libraries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 54 publications
3
97
0
4
Order By: Relevance
“…The observed effects of CP 7 provide further evidence of the previously demonstrated importance of alternating L-and D-amino acids in cyclopeptides. [28,29] The above killing curve results are consistent with the rapid killing rates associated with the detergent-like mode of action on the bacterial membrane. The microbial membrane disrupting effect of these cationic amphipathic cyclopeptides could provide general accessibility into the bacteria.…”
Section: Time Course Assaysupporting
confidence: 76%
“…The observed effects of CP 7 provide further evidence of the previously demonstrated importance of alternating L-and D-amino acids in cyclopeptides. [28,29] The above killing curve results are consistent with the rapid killing rates associated with the detergent-like mode of action on the bacterial membrane. The microbial membrane disrupting effect of these cationic amphipathic cyclopeptides could provide general accessibility into the bacteria.…”
Section: Time Course Assaysupporting
confidence: 76%
“…[4][5][6][7][8][9][10] It has been demonstrated using experimental and theoretical studies that a CPNT embedded in a lipid bilayer can act as an active transporter for various molecules. [4][5][6][7][8][11][12][13] Granja et al showed that 3 is characterized as the alternating Cα and mid-Cα regions. The plane formed by the Cα atoms in a CP is called the Cα plane.…”
Section: Introductionmentioning
confidence: 99%
“…The result is similar to the effect of high potentials on charged cyclic peptides. [9] The product of the electrical distance (d) and the charge associated with CB6 (z) was derived from the voltage dependence of K …”
mentioning
confidence: 99%